Advancements in Sports Medicine - Chen, Jiwu; Sun, Yaying (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the current progress in sports medicine, with a specific interest in surgery, exercise therapy, and multi-disciplinary research. With the advancement of society, more attention is paid to the quality of life, which emphasizes the importance of sports and exercise. Correspondingly, there is a great need for sports medicine. This issue collected novel findings on sports medicine in surgery, conservative therapy, and the application of exercise training in other disorders